Pengaruh Level Substitusi Jagung Giling dengan Tepung Kulit Pisang Hasil Fermentasi dalam Pakan Konsentrat dan Imbuhan Zn Biokomplek terhadap Status Fisiologis Sapi Bali Jantan Penggemukan - Galla, Oksen Tuang; Sobang, YohanisU.L.; Rosnah, Upik S. (Animal Agricultura, 2024)
This research aims to determine the effect of the level of substitution of ground corn with fermented banana peel flour in concentrate feed and biocomplex Zn additives on the physiological status of fattening male Bali cattle. The 12 bulls that will be used in this research are aged 1-1.5 years and weigh 138-149.5kg (x=145.3kg). For the experimental research method, a Completely Randomized Design (CRD) was used with 4 treatments and 3 replications. The treatments in this study were P0= Forage 70% + concentrate 30% without substitution (control) + Zn biocomplex, P1= Forage 70% + concentrate 30% (substitution of ground corn with TKPF 25%) + Zn biocomplex, P2= Forage 70 % + concentrate 30% (substitution of ground corn with TKPF50%) + Zn biocomplex. P3= Forage 70% + concentrate 30% (substitution of ground corn with KPF 75%) + Zn biocomplex. The data obtained analysis calculated using analysis of variance. Based on the research results, the average rectal temperature (OC) value was obtained for P0=38.20±0.591, P1=38.75±0.59, P2=37.87±0.60 and P3=38.46±0.89, Heart rate (times/minute) P0=70.73±5.50, P1=68.40±6.08, P2=67.40±5.29, and P3=66.07±2.51, Respiratory frequency (times/minute). P0=27.87±4.04, P1=29.53±6.42, P2=28.53±5.68, and P3=28.87±5.03, The results of the analysis showed that the treatment had no significant effect (P>0.05) on the physiological status of bali fattening cattle.